2018
DOI: 10.3389/fmicb.2018.01904
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Protein Cj0371 Inhibits Chemotaxis of Campylobacter jejuni

Abstract: cj0371 is a novel gene that is associated with Campylobacter jejuni virulence, and an isogenic mutant of cj0371 showed hyper chemotaxis and motility. Chemotactic motility is an important virulence factor and is involved in C. jejuni pathogenesis. Campylobacter sp. has specific variations of the common chemotaxis components, including histidine autokinase CheA, coupling scaffold protein CheV, chemotaxis response regulator protein CheY and several chemoreceptor proteins. In this study, we used immunoprecipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Next to the six core proteins mentioned above, additional proteins were identified that are present in some but not all pathways, as exemplified by the CheD deamidase, the CheW‐REC domain fusion protein CheV or the CheC, CheZ and CheX phosphatases (Wuichet and Zhulin, 2010). Furthermore, the scientific community keeps identifying additional proteins that participate in some signalling cascades (Lertsethtakarn et al ., 2015; Xu et al ., 2016; Du et al ., 2018). The second level of complexity lies in the fact that bacteria frequently have multiple pathways that are composed of homologous signalling proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Next to the six core proteins mentioned above, additional proteins were identified that are present in some but not all pathways, as exemplified by the CheD deamidase, the CheW‐REC domain fusion protein CheV or the CheC, CheZ and CheX phosphatases (Wuichet and Zhulin, 2010). Furthermore, the scientific community keeps identifying additional proteins that participate in some signalling cascades (Lertsethtakarn et al ., 2015; Xu et al ., 2016; Du et al ., 2018). The second level of complexity lies in the fact that bacteria frequently have multiple pathways that are composed of homologous signalling proteins.…”
Section: Introductionmentioning
confidence: 99%
“…. Furthermore, the upregulation of Cj0371 in isolate C. jejuni 286, but not in isolate C. jejuni NCTC11168, potentially influences the virulence of this isolate, as activation of this protein has a negative role on Campylobacters chemotaxis(Du et al, 2018).which is only produced in C. jejuni NCTC11168, is co-expressed with the fibronectin binding protein CadF (string-db.org), suggesting a possible link towards the increased fibronectin binding in this isolate. Four other virulence proteins were present in C. jejuni a number of putative virulence proteins were uniquely upregulated in the presence of L-fucose in C. jejuni 286, including exotoxin CdtC and the enterochelin uptake periplasmic binding protein CeuE.…”
mentioning
confidence: 96%
“…Interestingly, Cj0371 is considered an "anti-virulence gene", as it plays a negative role on Campylobacters chemotaxis. In the study ofDu et al (2018), the authors hypothesized that functions encoded by such genes may support colonization and coexistence of Campylobacter in animal hosts, including chickens(Du et al, 2018). However, these findings do not directly provide a link with in vitro virulence data obtained with C. jejuni 286, as cells precultured in MEMα, MEMαF and MEMαA medium showed comparable low Caco-2 invasion and fibronectin binding capacity.…”
mentioning
confidence: 98%